Chronic coronary artery occlusion: when does the benefit outweigh the risk? - A. G. Badoyan; D. A. Khelimsky; A. A. Shermuk; O. V. Krestyaninov; A. S. Bobrova; Sh. Sh. Fatulloeva; A. K. Turdubaev (Российский кардиологический журнал)
Today, the treatment of patients with chronic coronary occlusion is one of the most difficult problems in interventional cardiology. This is due not only to the technical difficulties of endovascular recanalization, but also to the difficulty in selecting patients for whom revascularization will be beneficial. Due to the low evidence base and the conflicting results of large clinical trials, these patients are rarely referred for endovascular recanalization. The purpose of this article is to review the literature and systematize relevant knowledge on the management of patients with chronic coronary occlusion.